Psychological growth following adversity: the role of social support - Durkin, John (2010)
The thesis begins with a review of the trauma literature as it relates to fire and rescue work and the attention given to the negative psychological consequences of involvement in such work. Clinical authorities warn of the psychological harm caused by exposure to traumatic incidents despite the recognition that psychological growth often follows adversity. To address this, firefighters were used in a series of studies to investigate the role of social support in facilitating growth. A philosophical overview of current understandings of trauma and growth was made along with the methodology chosen to pursue this investigation.